1997
DOI: 10.1046/j.1365-3083.1997.d01-389.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modelling of HLA‐DQ Suggests a Mechanism of Resistance in Type 1 Diabetes

Abstract: Genetic resistance and susceptibility to insulin-dependent diabetes mellitus (IDDM) have been associated with the HLA class II region on chromosome 6. In many races, the DQB1*0602 allele has been observed at a decreased frequency in IDDM, suggesting a protective role. A DNA sequence analysis of five patients, previously typed as having allele DQB1*0602, revealed sequence variation: one is DQB1*0603 and four possess unique sequences related to DQB1*0602 (one patient) or DQB1*0603 (three patients). Samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
3

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
0
22
3
Order By: Relevance
“…We speculate that a difference in hydrophobicity of the peptide binding groove between the protective DQA1*06 alleles compared with the risk factor alleles may result in the binding of antigens of higher hydrophobicity to the protective alleles. Although in some immune-mediated diseases HLA risk factors have been shown to have higher affinity for inciting antigens, in other cases autoantigens may have higher affinity for protective factor alleles (27,28). Therefore, under some conditions, a tight peptide-MHC binding may result in elimination of autoreactive T cell clones from the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that a difference in hydrophobicity of the peptide binding groove between the protective DQA1*06 alleles compared with the risk factor alleles may result in the binding of antigens of higher hydrophobicity to the protective alleles. Although in some immune-mediated diseases HLA risk factors have been shown to have higher affinity for inciting antigens, in other cases autoantigens may have higher affinity for protective factor alleles (27,28). Therefore, under some conditions, a tight peptide-MHC binding may result in elimination of autoreactive T cell clones from the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if inheritance of T1D MHC susceptibility genes is recessive, why are some protective alleles, such as HLA-DRB1*1501 and/or -DQB1*0602 [16][17][18], occasionally found in T1D patients? One possibility is that an ancient crossover produced a HLA-DRB1*1501-susceptibility DQB1 gene haplotype [16].…”
Section: Hla Allele and Haplotype Associations With T1dmentioning
confidence: 99%
“…It was reported that four patients with type 1A diabetes who were initially found to have the conventional DQB1*0602 with standard sequence-specific oligonucleotide (SSO) typing techniques actually had novel variants of this allele with sequencing (Hoover and Marta, 1997). This finding would suggest that the conventional DQA 1 *0 102-DQB I*0602 haplotype is never found in patients with type IA diabetes and that this haplotype confers absolute protection from the disease.…”
Section: Family Studiesmentioning
confidence: 99%